Adrenal mass: Unusual presentation and outcome - Raghu Sampally Ramareddy; Anand Alladi (Indian Journal of Medical and Paediatric Oncology)
Aim: Adrenal mass may be functioning or nonfunctioning with varied clinical presentations. This study aimed to report the nature and management of uncommon adrenal mass and to review literature. Materials and Methods: This was an retrospective observational analysis of children with uncommon adrenal mass admitted during 2009–2015. Clinical features, investigations, and management of patients were analyzed. Results: Among six, two each were adolescent and neonate, and one each was young infant and prenatal. Clinical presentation was variable; hypertensive retinopathy,[1] virilization[1] and bleeding diathesis,[1] antenatal suprarenal mass,[1] prenatal adrenal angiolipoma,[1] and spontaneous resolution of Stage III suprarenal mass.[1] Ultrasound and contrast-enhanced computed tomography revealed well-defined, heterogeneous adrenal mass. Size varied from 2 to 15 cm. Urinary metanephrine and serum testosterone were raised in adolescent hypertensive boys and virilized girls, respectively. Laparoscopy-assisted adrenalectomy was done in two and other four were managed conservatively. Histopathology of tumor revealed pheochromocytoma and borderline oncocytoma. Spontaneous resolution of adrenal mass had varied etiology; adrenal hemorrhagic lesion,[1] simple cyst,[1] neuroblastoma.[1] Follow-up varied from 3 months to 2 years. All patients were asymptomatic on last follow-up. Conclusion: Close clinical follow-up, contrast-enhanced tomography, and limited/specific endocrine work-up have definite role in the management of uncommon adrenal mass.